2020
DOI: 10.3389/fnins.2020.574234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine on the Immature Neurons of the Adult Rat Piriform Cortex

Abstract: The layer II of the adult piriform cortex (PCX) contains a numerous population of immature neurons. Interestingly, in both mice and rats, most, if not all, these cells have an embryonic origin. Moreover, recent studies from our laboratory have shown that they progressively mature into typical excitatory neurons of the PCX layer II. Therefore, the adult PCX is considered a “non-canonical” neurogenic niche. These immature neurons express the polysialylated form of the neural cell adhesion molecule (PSA-NCAM), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…The presence of dense core vesicles is very interesting and may suggest the presence of synaptic input from monoaminergic axons. In this line, a recent paper from our laboratory has shown that in the piriform cortex of adult rats, immature neurons express dopamine D2 receptors and dopaminergic axons are closely apposed to these cells (Coviello et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of dense core vesicles is very interesting and may suggest the presence of synaptic input from monoaminergic axons. In this line, a recent paper from our laboratory has shown that in the piriform cortex of adult rats, immature neurons express dopamine D2 receptors and dopaminergic axons are closely apposed to these cells (Coviello et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“… 176 Precise mechanisms of induction of these events are not clear yet, however, it was found that enzymatic depletion of PSA promotes the final stages of development of immature neuronal population, 175 the number of cells expressing PSA-NCAM induced by a dopamine receptor agonist decreases due to the differentiation of these cells associated with the loss of PSA-NCAM expression. 177 Then, newly-formed neurons become to be functionally integrated into the pre-existing neuronal ensembles in the cortex. 174 Almost similar mechanism seems to exist in the amygdala where dormant immature DCX+PSA-NCAM+ neurons persist for several years, but then may develop into mature neurons during adolescence.…”
Section: Integrity Of Brain Barriers and Control Of Adult Neurogenesismentioning
confidence: 99%
“…In this context, noradrenaline which controls different aspects of network plasticity involved in olfactory learning (Sullivan and Wilson, 1994;Rangel and Leon, 1995;Harley, 2004;Moreno et al, 2012) might be able to modulate the maturation of dormant precursors (Vadodaria et al, 2017). A role for additional monoamines in dormant precursor maturation has also been suggested (Coviello et al, 2020). Consequently, learning and adaptation in several adult brain regions devoid of neural stem cells might imply the introduction of new neurons arising through awakening of dormant precursors, possibly driven by the processing of salient experiences.…”
Section: Why Do We Need Dormant Precursors? Cognitionmentioning
confidence: 99%
“…In this regard, recent research on humans suggested a connection between dormant precursors in the amygdala and autism (Avino et al, 2018;Sorrells et al, 2019). Furthermore, research on animal models implies a relation between dormant precursor maturation and monoamine signaling (Vadodaria et al, 2017;Coviello et al, 2020), opening perspectives toward models of psychosis and/or depression.…”
Section: How Will We Know More About the Roles Of Dormant Precursors?mentioning
confidence: 99%